DIASPORA ORANG BALI: DINAMIKA SOSIAL-BUDAYA UMAT HINDU-BALI DI DESA KERTA BUANA - Siburian, Robert (Kebudayaan, 2016)
AbstractBalinese people have been living in Kerta Buana village since 1980, when they joinedtransmigration program. In fact, when they migrated to Kalimantan island, it was notsolely a physical, but also a cultural migration. Thus, they still perform their religiousrituals and customs like they used to in Bali so that the people surrounding Kerta Buanavillage do not need to go to Bali to learn and understand Balinese culture and religiousrituals of Hindu-Bali people. The settlement of Hindu-Bali people in a village will be asocial capital to actualize their culture. Related to the settlement of Hindu-Bali peoplein Kerta Buana village, the problems in this article, i.e.: (1) How social dynamics ofHindu-Bali people does in Kerta Buana village? (2) How kind of relationship have thatis built between Kerta Buana village and Bali island? The results of this research showsthat Hindu-Bali community in Kerta Buana village live in a community. So, it is easy tomanage it. The other thing is Hindu-Bali community in Kerta Buana village still carry outreligious rites and customs even though they live far from the area of origin. In fact, theyfabricated the culture in Bali in accordance with the conditions that exist in Kerta Buanavillage. The other thing, Hindu-Bali community still carry out rites and traditions, eventhough far distance from Bali island. In fact, they created Balinese culture for adaptedwith conditions in Kerta Buana village. AbstrakKeberadaan orang Bali di Desa Kerta Buana sudah sejak 1980, yaitu ketika merekamengikuti program transmigrasi. Pada saat mereka bertransmigrasi ke Pulau Kalimantan,ternyata yang bermigrasi tidak hanya fisik tetapi juga kebudayaan mereka. Dengankebudayaan yang ikut serta dengan mereka, ritual agama dan adat istiadat tetap merekalakukan seperti berada di Bali, sehingga masyarakat di sekitar Desa Kerta Buana tidakharus ke Bali untuk memahami kebudayaan dan ritual-ritual kegamaan orang HinduBali. Bermukimnya orang Hindu-Bali di suatu desa menjadi modal sosial untukmengaktualisasikan kebudayaannya itu. Terkait dengan keberadaan orang Hindu-Bali diDesa Kerta Buana, permasalahan yang diangkat dalam tulisan ini meliputi: (1) Bagaimanadinamika sosial orang Hindu-Bali di Desa Kerta Buana? (2) Bagaimana hubungan yangmereka bangun dengan daerah asal di Pulau Bali? Hasil penelitian menunjukkan bahwamasyarakat Hindu-Bali di Desa Kerta Buana hidup dalam satu komunitas sehingga mudahuntuk menggerakkannya ataupun mengelolanya. Hal lain adalah masyarakat Bali di DesaKerta Buana masih tetap melaksanakan ritual keagamaan dan adat istiadat kendati merekabermukim jauh dari daerah asal. Bahkan mereka merekayasa kebudayaan yang ada diBali sesuai dengan kondisi yang ada di Desa Kerta Buana.